A new species of Phyllodytes (Anura: Hylidae) from the Atlantic Rainforest of southern Bahia, Brazil - Vörös, Judit; Dias, Iuri Ribeiro; Solé, Mirco (Zootaxa, 2017)
We describe Phyllodytes amadoi sp. nov., a species of treefrog from the Atlantic Rainforest of southern Bahia, Brazil. The new species can be diagnosed by its small body size (SVL 15.6–23.0 mm) and advertisement call with high dominant frequency (3.789–4.306 Hz). It is known from one locality in the Private Reserve of Natural Heritage Ararauna, in the municipality of Una (15° 18' 38.3" S, 39° 9' 55.9" W, 96 m a.s.l.).